Wage differentiation and unemployment in the districts of the Czech Republic - Kamila Fialová (Charles University in Prague, Institute of Economic Studies (IES), 2008)
This paper concerns the labour market differences among the 77 districts of the Czech Republic. There was a remarkable trend of increasing regional labour market differentiation in the 1990's, however, the patterns of differentiation have stabilised since then. The first part of the paper aims to describe the regional differentiation in wages and unemployment on the descriptive method basis. The other part of the study attempts to explain the differences in wages by an econometric model. We focus on the effect of unemployment rate, representing an exogenous factor of the region itself. The model's specification arises out of the general concept of wage differentiation and the concept of the wage curve. According to our analysis there were several factors of influence on the regional wage differentiation in 2001: educational structure of the population, employment structure of the regional economy, degree of economic concentration, and district rate of unemployment. The coefficient of the unemployment elasticity of wages equals 0.08, which can be considered as evidence of the existence of the wage curve in the districts of the Czech Republic. Moreover, the relationship is stronger in the low-unemployment districts.
Keywords: E24; J31; J64; R23; 330; regional disparities; wages; unemployment; wage curve; Lohndifferenzierung; Regionale Arbeitslosigkeit; Regionale Lohnstruktur; Lohnkurve; Theorie; Tschechische Republik